Fertility Desire of Working Women in Kathmandu - Pradhan, A; Pandey, S (Journal of Nepal Health Research Council, 2011)
Background: This study is done to describe the fertility pattern and factors associated with unmet desire for additional children among women working in formal and informal sector in Kathmandu, Nepal. Methods: This is a cross-sectional study. Married 177 women in reproductive age group, with at least one child are selected using purposive sampling. Housewives without paid job are excluded. Interview using semi structured questionnaire is conducted. Results: Around 14 percent of women want additional children however due to various reasons they do not intend to have another. Women in age group of 25-29 followed by 30-34 years of age have higher desire for more children as compared to women in more than 40 years of age. Women who earn 25000-33000 Rupees per month have significantly more desire for another child. Conclusions: Childcare time and economic conditions play vital role in fertility desire among working women. Family help is available to most of the women to care their children. These women wish more facilities at workplace during child bearing and rearing period. Key words: fertility desire, unmet desire for additional child, working women